2010
DOI: 10.1007/s12029-010-9214-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential Value of Estrogen Receptor Beta Expression in Colorectal Carcinoma: Interaction with Apoptotic Index

Abstract: The study results reinforce the importance of the estrogen receptor beta rather than the estrogen receptor alpha in colorectal cancer. Lack of estrogen receptor beta expression is associated with loss of differentiation and decreased apoptosis. Future studies should include validation of estrogen receptor beta as a prognostic marker and exploration of its role as a target in the management of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Results of our study are in line with studies that associated ER β -negative tumours with advanced tumour stages (Jassam et al , 2005; Elbanna et al , 2012). We did not observe a significantly different expression of ER β in relation to tumour differentiation as reported by Konstantinopoulos et al (2003).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results of our study are in line with studies that associated ER β -negative tumours with advanced tumour stages (Jassam et al , 2005; Elbanna et al , 2012). We did not observe a significantly different expression of ER β in relation to tumour differentiation as reported by Konstantinopoulos et al (2003).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the ER α , which has a major role in breast cancer development (Cuzick et al , 2011), treatment and prognosis (Davies et al , 2011), can be found only at very low levels in normal colorectal tissue (Kennelly et al , 2008). Results of previous studies showed that loss of ER β expression in CRC is associated with poorer differentiation of tumours and more advanced cancer stages (Konstantinopoulos et al , 2003; Jassam et al , 2005; Elbanna et al , 2012). …”
mentioning
confidence: 96%
“…ERβ has a crucial role in colonic-cell homeostasis, including modulation of proliferation and organised cell death (Kennelly et al, 2008). Some previous studies have showed that loss of ERβ expression in CRC is associated with poorer differentiation of tumors and more advanced cancer stages (Jassam et al, 2005;Elbanna et al, 2012). And a previous study demonstrated that ERβ-positive colorectal tumors were associated with a better overall survival (Fang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A potential mediator of estrogen effects is the estrogen receptor-b (ESR2), which is the primarily expressed estrogen receptor in the large intestine (1). Loss of ESR2 expression in tumor tissue of patients with colorectal cancer has been associated with poorer differentiation of tumors and more advanced cancer stages (7)(8)(9)(10). However, it has also been postulated that endogenous and exogenous sex hormones may have differential effects on the development of colorectal cancer (6), as high levels of endogenous estrogens have been found to be associated with an increased risk for colorectal cancer (11,12).…”
Section: Introductionmentioning
confidence: 99%